Affective States, Coping and Mutual Understanding in Russian Families During the Coronavirus Disease 2019 Pandemic Lockdown - Leonova, Elena V.; Khavylo, Alexey V. (Frontiers in Psychology, 2021)
The purpose of the empirical study (April–May 2020) was to determine the type and level of affect, specifics of coping styles during the coronavirus disease 2019 (COVID-19) pandemic lockdown, as well as mutual understanding between parents and children. We hypothesized that the combination of positive and negative affect magnitude is a factor in well-being and mutual understanding with children, as well as the coping style during the lockdown. The study involved 705 respondents aged 16–77, including 435 parents living with children under 16. Personal traits, positive and negative affect, coping styles, and well-being were studied by Ten-Item Personality Inventory (TIPI)-RU, Positive and Negative Affect Scale (PANAS)-RU, Brief COPE, Satisfaction with Life Scale (SWLS), respectively. Mutual understanding was studied using a self-report questionnaire. Cluster analysis (k-means method) was used to divide the sample into clusters in accordance with the combination of positive and negative affect. According to the data obtained, parents from the “positive-affective” cluster have much better mutual understanding with both younger and older children than participants from other clusters.